Palms of New Guinea - Baker, William J. 1972-; Barfod, Anders S.; Cámara-Leret, Rodrigo; Dowe, John Leslie 1951-; Heatubun, Charlie D.; Petoe, Peter; Turner, Jessica H.; Zona, Scott 1959-; Dransfield, John 1945- (Kew Publishing, Royal Botanic Gardens, Kew, 2024)
New Guinea is the world's largest tropical island and a globally significant biodiversity hotspot. Palms dominate the rainforests of New Guinea, from exquisite, forest floor palmlets to graceful canopy giants, and are vital for local people who depend on them for survival. Palms of New Guinea is the first comprehensive account of these immensely important plants and includes all 250 species, covering their taxonomy, identification, distribution, habitat, conservation status and much more. Richly illustrated throughout with over 650 colour photographs, 250 distribution maps and line drawings for all species prepared by botanical artist Lucy T. Smith. Written by nine scientific experts, this is an essential companion for anyone studying or growing palms from the New Guinea region.--Back cover
Keywords: Ökologie; Ethnobotanik; Systematik; Palmen; Neuguinea; Palms / New Guinea; Palmiers / Nouvelle-Guinée; Bestimmungsbuch; Verzeichnis